NSAID–Gut Microbiota Interactions - Maseda, Damian; Ricciotti, Emanuela (Frontiers in Pharmacology, 2020)
Nonsteroidal anti-inflammatory drugs (NSAIDs) relief pain, inflammation, and fever by inhibiting the activity of cyclooxygenase isozymes (COX-1 and COX-2). Despite their clinical efficacy, NSAIDs can cause gastrointestinal (GI) and cardiovascular (CV) complications. Moreover, NSAID use is characterized by a remarkable individual variability in the extent of COX isozyme inhibition, therapeutic efficacy, and incidence of adverse effects. The interaction between gut microbiota and host has emerged as a key player in modulating host physiology, gut microbiota-related disorders and metabolism of xenobiotics. Indeed, host-gut microbiota dynamic interactions influence NSAID disposition, therapeutic efficacy and toxicity. The gut microbiota can directly cause chemical modifications of the NSAID or can indirectly influence its absorption or metabolism by regulating host metabolic enzymes or processes, which may have consequences for drug pharmacokinetic and pharmacodynamic proprieties. NSAID itself can directly impact the composition and function of the gut microbiota or indirectly alter the physiological properties or functions of the host which may, in turn, precipitate in dysbiosis. Thus, the complex interconnectedness between host-gut microbiota and drug may contribute to the variability in NSAID response and ultimately influence the outcome of NSAID therapy. Herein, we review the interplay between host-gut microbiota and NSAID and its consequences for both drug efficacy and toxicity, mainly in the GI tract. In addition, we highlight progress towards microbiota-based intervention to reduce NSAID-induced enteropathy. Ultimately, we aim to contribute to construct a new kind of medical knowledge that integrates data on the host and on the microbiota to improve therapeutic outcomes.